Problema autenticității în proza narativă a lui Anton Holban - Teodorowicz, Justyna (Studia Romanica Posnaniensia, 2023)
The article discusses the problem of authenticity in the narrative prose written by Anton Holban, a Ro-manian author of the interwar period. Holban, one of the most innovative writers of his time, contributed to the development of the psychological novel. His work has been appreciated by literary critics from the very beginning. We consider the concept of authenticity to be one of the most important in his novels. Strongly autobiographical, they reflect man’s desperate efforts, through insightful and meticulous analysis, to discover the truth about himself and the world about him. However, absolute authenticity proves impossible to achieve, both for the narrator and the writer himself.